Respuesta :

Answer:

-213

not in d option though check d question

Step-by-step explanation:

h(r) = 23r − 6

h(-9) = 23(-9) - 6

= -207 - 6

= -213

Answer:

-213

Step-by-step explanation:

If h(r) = 23r − 6, then, if we choose r = 2 as an example (only), then:

If h(2) = 23(2) − 6 = 46 - 6 = 40

Using the same approach, we substitute -9 for r, obtaining:

If h(-9) = 23(-9) − 6 = -207 - 6 = -213

This does not match any of the given possible answers.  Please ensure that you have copied down the problem and possible answers accurately.